Perancangan Interior French Fine Dining Restaurant di Surabaya - Bambang Gozaly; Grace Mulyono (Intra, 2014)
This design would like to design the interior of a restaurant that is growing and in demand by the people of Surabaya. One type of restaurant that is growing rapidly is currently fine-dining restaurant. Is a fine-dining restaurant industry food and beverage services are managed commercially and professionally with exclusive services. In this scheme will apply the elements of interior decoration to a French restaurant looks very high quality with elegant atmosphere to be created by the restaurant with the feel of the design concepts that have been defined. This decoration design concept will be adapted to the nuances of French people who are more interested in wanting to try French food with a French atmosphere.